Technologiceskaja model' upravlenija techniceskoj podgotovkoj v trojnom pryžke - Ogandzhanov, A. L.; Kosikhin, V. P.; Tyagachev, A. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Modern equipment based on IT allows to increase the efficiency and accuracy of the control of jumper-athletes` special preparation. The following research is related to the development of the method of controlling the technical and physical preparation of qualified athletes which is based on the cathode ray device known as "OptoJump Next". In cooperation with model characteristics the following control method allows to make a conclusion about the development of individual sides of the special preparation in athletes and as the result to carry out the corrections of the preparation process.